The Role of Sasak Women in Community Social Development in Nusa Tenggara Barat - Sukron Azhari; Ariadi, Izwan; Ariwidodo, Eko; Masroer, Masroer (Universitas Islam Negeri Madura, 2022)
This article discusses gender, especially in women’s job qualifications, and provides opportunities for women in society. Gender issues are expected to be addressed, but what about the people of Wakan village who still use patriarchal culture daily? It causes women to be unable to work according to their talents. This study refers to Foucault's theory of knowledge and power regime. In contrast, the research method uses descriptive qualitative research, so the data collection technique uses a depiction of people’s lives that are happening now. The results show that women in Wakan Village still experience discrimination by men, especially in society, both in public and other spaces. It started from the community’s belief in seeing these women so that the role of women was still minimal in any case. Even though both men and society provide opportunities for women, every opportunity is still supervised by men, so all opportunities and roles of women cannot equal the roles of men, which causes women to be subordinated.